Postharvest handling and processing of coffee beans at UKM Akarosta, Tana Toraja Regency - Pista; Diyah Yumeina; Ahmad Munir; Gemala Hardinasinta (Salaga Journal, 2023)
Postharvest handling and coffee processing must be carried out based on SNI standards to produce good quality and to increase selling value. In Tana Toraja Regency, there are various UKM engaged in the coffee processing industry but not many have analyzed the quality of the coffee produced. The purpose of this research is to know the postharvest handling and processing of coffee bean at UKM Akarosta and compare the proper postharvest handling process of coffee beans based on SNI standards. The results showed that the postharvest method carried out by farmers in Pasang Village, South Makale District, Tana Toraja Regency is a semiwash method which included harvesting, sorting, peeling fruit skins, washing, drying then stripping horn skins, sorting, roasting, grinding and packaging by UKM Akarosta. The postharvest process carried out by farmers has met with SNI. The quality of the coffee beans produced has met the SNI standard quality of coffee beans No. 01-3542-2004.